UPSKILLING AND RESKILLING STRATEGIES FOR EMPLOYEES IN INDUSTRY 5.0 - Dr. Sagar Manjunath,; Dr. Ranjith P V,; Dr. Kiran Kumar Thoti,; Dr. Oscar Abhishek, (The Bioscan, 2026)
In the context of rapid technological advancements and evolving job requirements, organizations increasingly emphasize upskilling and reskilling initiatives to enhance workforce competencies. The present study examines the impact of upskilling and reskilling strategies on workforce competency levels among software professionals. A descriptive and quantitative research design was adopted to achieve the objectives of the study. Primary data were collected from 181 software employees working in Karnataka, specifically in the Bengaluru and Mysuru regions, using a structured questionnaire developed on a five-point Likert scale ranging from 5 = Strongly Agree to 1 = Strongly Disagree. The respondents belonged to the age group of 23–35 years, representing early- and mid-career professionals in the software industry. The sample consisted of 101 female and 80 male respondents, ensuring adequate gender representation. The data were analysed using appropriate statistical techniques to assess the relationship between upskilling and reskilling strategies and workforce competency levels across cognitive, social, and technical domains. The findings reveal that both upskilling and reskilling strategies have a positive and statistically significant influence on workforce competencies, with upskilling demonstrating a comparatively stronger impact. The study underscores the critical role of continuous skill development initiatives in enhancing employee capabilities and improving organizational adaptability in a dynamic digital environment. The results offer practical implications for human resource managers, learning and development professionals, and policymakers in designing effective workforce development frameworks for the software industry in Karnataka. Keywords Upskilling, Employee Productivity, Reskilling, Software Industries, Management